Sour Cherry (Cerasus vulgaris Miller) Kernel Oil as the Novel Functional Edible Oil: Sensory Evaluation and Antioxidant and Physicochemical Properties - Maryam Kazempour-Samak; Ladan Rashidi; Mehrdad Ghavami; Anoosheh Sharifan; Fakhrisadat Hosseini (Journal of Food Quality)
This study aims to extract oil from fresh sour cherry kernel (Cerasus vulgaris Miller) using the cold press method. The oil content and moisture were obtained as 31.89% and 4%, respectively. The organoleptic assessment of the oil was acceptable and the free fatty acid value was obtained as 1.36 (mg KOH/g oil). In addition, peroxide value and anisidine index of sour cherry kernel oil were obtained as 0.99 meqO2/kg oil and 0.15, respectively. The predominant fatty acids were linoleic acid (42.34%), oleic acid (35.45%), α-eleostearic acid (9.34%), and palmitic acid (6.54%), respectively. The kernel oil contained nine major triacylglycerols consisting of OLL (20.44%), OOL (16.99%), LLL (8.20%), LLEl (7.28%), PLO (7.24%), OElO (5.03%), OOO (4.70%), ElLO (4.54%), PLL (4.35%), and POO (3%), respectively. The most abundant sterol compounds were β-sitosterol (83.55%), ∆5-avenasterol (6.8%), sitostanol (4.8%), campesterol (3.5%), and stigmasterol (0.53%), respectively. Also, antioxidant activity, total phenol content (TPC), total anthocyanin content (TAC), total flavonoid content (TFC), total tannin content (TTC), and total tocopherol content were obtained as 73.22%, 33.44 mg GA/g dry matter, 177.84 mg/L, 46.37 mg/g dry matter, and 1.21 mg GA/g dry matter, 832.5 mg/kg oil, respectively. The amount of amygdalin in the oil sample was not detectable.